Atividades anti-Candida e análise da citotoxidade do extrato da folha da Schinopsis brasiliensis Engl. - Jovito, Vanessa de Carvalho (2016)
Given the need to implement new therapeutic agents for the treatment of infections caused by Candida spp., the search for natural products grows worldwide. Against this background extracts obtained from Schinopsis brasiliensis Engl. represent potential sources of chemical agents with antifungal effect, considering their recognized bacterial activity. Objective: To evaluate the antifungal, anti-biofilm and cytotoxic potential of the rotavaporated extract of S. brasilienses leaf on Candida spp. Methods: Minimal Inhibitory Concentration - MIC and Minimum Fungicide - CFM were determined on 6 Candida strains by the microdilution technique in 96-well plates. The growth inhibition kinetics of C. albicans ATCC 60193 at different times in the MIC, MIC x 2 and MIC X 4 concentrations were evaluated. The anti-biofilm evaluation was determined in microdilution plates with evaluation of inhibition of formation and reduction of Biofilms ripe uniespecies or multispecies of 24 and 48 hours. The synergism was evaluated by the checkerboard method. Cytotoxicity was performed on human blood cells. The data were analyzed by Tukey, Mann-Wihitney, Kruskall Wallis, ANOVA and post-hoc paired T-test with p <0.05. Results: For the Minimum Inhibitory Concentration the leaf extract of S. brasiliensis presented antifungal activity against all The Candida species evaluated. There was a reduction in formation and in the mature biofilms uni and multispecies for the periods of 24 and 48h. In the kinetics only the MIC concentration x 4 presented results, being the best result of the extract from six hours (p <0.01). At all concentrations used in the study up to 1250 μg / mL the extract did not show cytotoxicity in human cells. Conclusion: The extract of the leaf of S. brasiliensis has antifungal activity on strains of the genus Candida, showing, in general, fungicidal action, especially after six hours of contact with the microbial cells and antibiofilm effect constituted by Candida spp. (Uni and multispecies), with ability to inhibit the formation and reduction of mature biofilm without cytotoxicity on peripheral blood mononuclear cells.